2009
DOI: 10.1038/sj.bjc.6605076
|View full text |Cite
|
Sign up to set email alerts
|

FDG uptake is a surrogate marker for defining the optimal biological dose of the mTOR inhibitor everolimus in vivo

Abstract: This study aimed to test whether [ 18 F]fluoro-D-glucose (FDG) uptake of tumours measured by positron emission tomography (PET) can be used as surrogate marker to define the optimal biological dose (OBD) of mTOR inhibitors in vivo. Everolimus at 0.05, 0.5, 5 and 15 mg kg À1 per day was administered to gastric cancer xenograft-bearing mice for 23 days and FDG uptake of tumours was measured using PET from day 1 to day 8. To provide standard comparators for FDG uptake, tumour volume, S6 protein phosphorylation, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 24 publications
(26 reference statements)
1
23
0
Order By: Relevance
“…In the NCI-N87 xenografts, Ki67 expression did not differ between BEZ235-and Ctrltreated xenografts. Such contrasting results have been observed also in previous studies employing the NCI-N87 xenograft model, where no significant Ki67 suppression by mTOR inhibitors was observed despite antitumor activity and specific mTOR target regulation (24,46). As an alternative, we assessed TK1 expression which is likewise well established as a marker for cell proliferation (34).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the NCI-N87 xenografts, Ki67 expression did not differ between BEZ235-and Ctrltreated xenografts. Such contrasting results have been observed also in previous studies employing the NCI-N87 xenograft model, where no significant Ki67 suppression by mTOR inhibitors was observed despite antitumor activity and specific mTOR target regulation (24,46). As an alternative, we assessed TK1 expression which is likewise well established as a marker for cell proliferation (34).…”
Section: Discussionmentioning
confidence: 56%
“…PTEN loss was reported not to serve as a predictive biomarker for response to the mTOR inhibitor everolimus (45). Previous publications of our group showed that the phosphorylation status of the mTOR downstream target S6 does not necessarily predict efficacy of mTORC1 inhibitors in tumor models (44,46).…”
Section: Discussionmentioning
confidence: 99%
“…Mice received 10 mg/kg everolimus daily via intraperitoneal injection (10 mL/kg). The everolimus dosage used is based on previous efficacy studies in xenografted mice, in which 5 to 10 mg/kg daily resulted in unbound (active) everolimus plasma levels comparable with those reached in humans receiving 5 to 10 mg daily due to higher plasma protein binding and shorter T 1/2 values in mice (8,(19)(20)(21)(22).…”
Section: Compoundsmentioning
confidence: 99%
“…40 In fact, changes in glucose uptake as measured by FDG PET imaging have been used to optimize everolimus dosing in vivo. 41 To address the possibility that changes in FDG-PET scanning may serve as an early predictor of response or resistance to everolimus treatment, a phase 2 trial is on-going in which 60 patients with metastatic RCC will undergo FDG-PET imaging before and after initiating therapy with everolimus. The primary objective of this study is to determine if high basal FDG-avidity is predictive of greater likelihood of response to everolimus as determined by changes in RECIST-based tumor measurements after 8 weeks of therapy.…”
Section: Patient Selection Strategiesmentioning
confidence: 99%